Development of shrimp bouillon cubes from hairy shrimp or "suahe" (Metapenaeus ensis) - Tulio, Artemio Jr. Zabala; Guantes, Arnel C. (1990.)
ABSTRACT The feasibility of developing an acceptable shrimp bouillon cubes utilizing whole shrimp was investigated in the study. In phase I, shrimp powder was produced using the modified I.T.D.I> production procedure. Physico-chemical tests, sensory evaluation, and microbial examination were conducted on the shrimp powder produced from three production trials. Results of the physico-chemical tests showed the following average values: yield, 10.75%; moisture, 3.78% and rehydration, 3.45. On the other hand, results of the sensory evaluation revealed that the product of each production trial has a nearly light brown color, a just recognizable to characteristic shrimp odor and an almost very fine texture. Furthermore, it was rated almost "like moderately" for general acceptability. The results of the microbial examination indicated a negative microbial count/ In phase II, the shrimp powder was used as the main ingredient in the formulations of shrimp bouillon cubes. Two formulates were developed and the cubing process was standardized. The finished product were then subjected to proximate analysis, sensory evaluation and microbiological examination. test results revealed the following average proximate composition for Formulations I and II, respectively: moisture, 6.77%, and 7.03%; ash, 19.19% and 9.75%; crude fat, 12.92% and 17.45%; crude protein, 18.29% and 17.08%; crude fiber, 0.18% and 0.44%; and nitrogen-free extract, 42.65%, and 48.25%. Results of the sensory evaluation indicated that, except for color, there is no significant difference between the sensory attributes of the two products. Formulation I was described as having slightly yellowish-brown color. Both shrimp bouillon cube formulates were described as having an almost characteristics shrimp odor, an almost compact and smooth appearance, an almost regular cube shape, and a texture that is almost grainy. Furthermore, results of the sensory evaluation of instant shrimp soup prepared from each shrimp bouillon cube formulations indicated a just recognizable to characteristics shrimp odor, and flavor, an a rating of nearly "like moderately" to like "moderately" in terms of the general acceptability. Results of the microbiological examination revealed an increase in microbial load after the incorporation of other ingredients to the shrimp powder. the total plate count revealed a microbial load of 4,240/gm and 1,455/gm for Formulation I and II, respectively. On the other hand, yeast and mold count showed a load of 2,6755/gm and 995/gm for Formulation I and II, respectively.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Shrimps; Shrimp bouillon